Development of control system for robotic apple harvesting device - Pupin Daniil; Chilikin Andrey (E3S Web of Conferences, 2023)
This article focuses on the control system of a robotic device designed for efficient apple harvesting with minimal fruit damage. The developed device is equipped with specialized mechanisms and sensors aimed at reducing negative impacts on fruits during harvesting. A control system for the robotic device was developed, incorporating various sensors and modules. A module for determining the position of the grip arms was designed, consisting of a polymeric magnetic strip attached to a spiral-shaped cutout. A module to track the position of the grip arms was also developed, capable of indicating the current position of the grip arms, fully open and closed grip, as well as intermediate values. A module to monitor the grip force was designed, used to control the gripping force applied to the fruit. A current sensor was connected to the winding of the linear actuator motor to measure the force. Increasing the force applied by the grip arms to the fruit results in higher current flowing through the linear actuator motor winding. By reading the current sensor data, the degree of compression on the fruit is determined. During testing of the control system modules and sensors, it was found that the grip arm angle position module has the highest sensitivity in the range of 0 to 90 degrees. The obtained data after calibration enable the control of the degree of grip arm opening. The grip arm position module allowed controlling and adjusting the grip arm position with an accuracy of up to 2 mm. A control system for a robotic grip for apple harvesting was developed. Various modules contributing to efficient apple harvesting were designed. One of the key modules is the grip force control module, which regulates the degree of fruit compression during robotic fruit harvesting, thus minimizing fruit damage.